Acute Tubulointerstitial Nephritis in a Patient on Anti-Programmed Death-Ligand 1 Triggered by COVID-19: A Case Report. (May 2021) - Buyansky, Dimitry; Fallaha, Catherine; Gougeon, François; Pépin, Marie-Noëlle; Cailhier, Jean-François; Beaubien-Souligny, William
Rationale: Immune checkpoint inhibitors are monoclonal antibodies used in the treatment of various types of cancers. The downside of using such molecules is the potential risk of developing immune-related adverse events. Factors that trigger these autoimmune side effects are yet to be elucidated. Although any organ can potentially be affected, kidney involvement is usually rare. In this case report, we describe the first known instance of a patient being treated with an inhibitor of programmed death-ligand 1 (anti-PD-L1, a checkpoint inhibitor) who develops acute tubulointerstitial nephritis after contracting the severe acute respiratory syndrome coronavirus 2. Presenting concerns of the patient: A 62-year-old patient, on immunotherapy treatment for stage 4 squamous cell carcinoma, presents to the emergency department with symptoms of lower respiratory tract infection. Severe acute kidney injury is discovered with electrolyte imbalances requiring urgent dialysis initiation. Further testing reveals that the patient has contracted the severe acute respiratory syndrome coronavirus 2. Diagnosis: A kidney biopsy was performed and was compatible with acute tubulointerstitial nephritis. Interventions: The patient was treated with high dose corticosteroid therapy followed by progressive tapering. Outcomes: Rapid and sustained normalization of kidney function was achieved after completion of the steroid course. Novel findings: We hypothesize that the viral infection along with checkpoint inhibitor use has created a proinflammatory environment which led to a loss of self-tolerance to renal parenchyma. Viruses may play a more important role in the pathogenesis of autoimmunity in this patient population than was previously thought.